Thyroid specific ablation of the Carney Complex gene, PRKAR1A, results in hyperthyroidism and follicular thyroid cancer - Pringle, Daphne R. (2012)
Thyroid cancer is the most common endocrine malignancy in the population, and the incidence of this cancer is increasing at a rapid rate. Although genetic analysis of papillary thyroid cancer (PTC) has identified mutations in a large percentage of patients, the genetic basis of follicular thyroid cancer (FTC) is less certain. Thyroid cancer, including both PTC and FTC has been observed in patients with the inherited tumor predisposition Carney Complex (CNC), caused by mutations in PRKAR1A. In order to investigate the role of loss of PRKAR1A in thyroid cancer, we generated a tissue-specific knockout of Prkar1a in the thyroid. We report that the resulting mice are hyperthyroid and developed follicular thyroid neoplasms by one year of age, including FTC in over 40% of animals. These thyroid tumors showed a signature of pathway activation different from that observed in other models of thyroid cancer. In vitro cultures of the tumor cells indicated that Prkar1a-null thyrocytes exhibited growth factor independence and suggested possible new therapeutic targets. Overall, this work represents the first report of a genetic mutation known to cause human follicular thyroid cancer that exhibits a similar phenotype when modeled in the mouse. In addition to adding to our knowledge of the mechanisms of human follicular thyroid tumorigenesis, this model is highly reproducible and may provide a viable mechanism for the further clinical development of therapies aimed at follicular thyroid cancer.